Incomplete lineage sorting and introgression in the diversification of Chinese spot-billed ducks and mallards - Wang, Wenjuan (Curr Zool, 2019)
Incomplete lineage sorting and introgression are 2 major and nonexclusive causes of species-level non-monophyly. Distinguishing between these 2 processes is notoriously difficult because they can generate similar genetic signatures. Previous studies have suggested that 2 closely related duck species, the Chinese spot-billed duck Anas zonorhyncha and the mallard A. platyrhynchos were polyphyletically intermixed. Here, we utilized a wide geographical sampling, multilocus data and a coalescent-based model to revisit this system. Our study confirms the finding that Chinese spot-billed ducks and Mallards are not monophyletic. There was no apparent interspecific differentiation across loci except those at the mitochondrial DNA (mtDNA) control region and the Z chromosome (CHD1Z). Based on an isolation-with-migration model and the geographical distribution of lineages, we suggest that both introgression and incomplete lineage sorting might contribute to the observed non-monophyly of the 2 closely related duck species. The mtDNA introgression was asymmetric, with high gene flow from Chinese spot-billed ducks to Mallards and negligible gene flow in the opposite direction. Given that the 2 duck species are phenotypically distinctive but weakly genetically differentiated, future work based on genome-scale data is necessary to uncover genomic regions that are involved in divergence, and this work may provide further insights into the evolutionary histories of the 2 species and other waterfowls.